Morphological assessment of method of postresection pericardial defect closure using fabric implant on basis of nanostructural nikelide titanium fiber - Ye. B. Topolnitsky (Bûlleten' Sibirskoj Mediciny, 2011)
Method of postresection pericardial defect closure using fabric implant on basis of nanostructural nikelide titanium fiber has been developed and tested on ten mongrels. Morphology of reclaim generated after pericardial reconstruction using fabric implant was studied. A new generated tissue has been shown to extend through implant and form single tissue reclaim, which keeps anatomico-physiological restoration of pericardial defect.